From Sustainable Finances to Faithful Investing: A moral proposal according to the Catholic Social Thought - Fernández-Fernández, José L. (Archīum Ateneo, 2022)
Finance is an element of economic life that can contribute to shaping a more humane, equitable and sustainable world; and finance oriented by reference to ESG criteria represents an encouraging step forward at the service of the Common Good. In this article we contrast finance from ESG criteria with Faithful Investing, more specifically, with the tradition of Catholic Social Thought (CST) and its criteria for ethical, responsible, and sustainable investing decisions. Therefore, we try to go beyond, opening a path towards a more explicit way of acting in financial markets from a moral option rooted in religion: Faithful Investing. The paper begins by delimiting differences among ambits of reality in the field of meta-financial investing options. So, the first section, using a Logical-symbolic notation, presents a triple thesis that serves as a framework for the rest of the paper. From it, the concept of Faithful Investing is demarcated, by contrasting it with other related concepts: ESG, SRI, and EI. After underlining the relevance of the moral dimension of financial activity, and after presenting in depth the principles of the CST, the paper presents the point of view of this tradition about finance. We conclude the paper by showing some empirical evidence of how Faithful Investing is not only attractive as a good moral option, but it is also, because of profitable portfolios, well diversified and with persistent and sustainable returns over time.